How do Italian pediatric endocrinologists approach gender incongruence? - Silvia Ciancia; Lorenzo Iughetti (BMC, 2023)
Abstract Background Gender incongruence (GI) is a term used to describe a marked and persistent incompatibility between the sex assigned at birth (SAAB) and the experienced gender. Some persons presenting with GI experience a severe psychological distress defined as gender dysphoria (GD).. Although the prevalence of GI is probably underestimated, recently a great increase in numbers of transgender and gender diverse (TGD) youths presenting at the gender clinics has been registered. After a careful multidisciplinary evaluation and upon acquisition of informed consent from the youth and the legal guardian(s), puberty suppression can be started in TGD youths, followed by the addition of gender affirming hormones (GAH) by the age of 16 years. Although Italian specific guidelines are available, their application is often complex because of (among other reasons) lack of specialized centers and healthcare professional with experience in the field and the regional differences within the Italian healthcare system. Main body To investigate the care offered to TGD youths across Italy, we proposed a survey of 20 questions to the directors of the 32 Italian Centers of pediatric endocrinology participating to the Study Group on Growth and Puberty of the Italian Society of Pediatric Endocrinology (ISPED). Eighteen pediatric endocrinologists representative of 16 different centers belonging to 11 different regions responded to the survey. In the large majority of centers TGD youths are taken in charge between the age of 12 and 18 years and at least three healthcare professional are involved. Most of Italian pediatric endocrinologists follow only a very limited number of TGD youths and reference centers for TGD youths are lacking. Conclusion There is an urgent need for gender clinics (homogeneously distributed on the national territory) where TGD youths can access high standard care.